(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Biometric key technology is the organic combination of biometric encryption technology and traditional cryptography. Biometric key can directly encrypt data or encrypt key, with the character of portable use and not easily being stolen, forgotten and broken. This article provides an algorithm for generating key based on the fingerprint feature bit-strings, extracting feature information with bit-strings form as first step, generating key by the combination of this feature information and BCH error correcting code secondly. Experiments show that the algorithm can generate stable key of encryption on the premise of protecting the user's information. It can further improve the security strength and reach two-factors protection if the biometric key is stored in the smart card, which has certain practical value.